HIV incidence and risk factors for acquisition in HIV discordant couples in Masaka, Uganda: an HIV vaccine preparedness study. - Eugene Ruzagira; Symon Wandiembe; Andrew Abaasa; Agnes N Bwanika; Ubaldo Bahemuka; Pauli Amornkul; Matthew A Price; Heiner Grosskurth; Anatoli Kamali (PLoS ONE)
Objectives To determine the incidence of and risk factors for HIV acquisition in a cohort of HIV-uninfected partners from HIV discordant couples in Masaka, Uganda, and to establish its suitability for HIV vaccine trials. Methods HIV-uninfected adults living in HIV discordant couple relationships were enrolled and followed for 2 years. Interviews, medical investigations, HIV counseling and testing, syphilis and urine pregnancy (women) tests were performed at quarterly visits. Sexual risk behaviour data were collected every 6 months. Results 495 participants were enrolled, of whom 34 seroconverted during 786.6 person-years of observation (PYO). The overall HIV incidence rate [95% confidence interval (CI)] was 4.3 [3.1-6]; and 4.3 [2.8-6.4] and 4.4 [2.5-8] per 100 PYO in men and women respectively. Independent baseline predictors for HIV acquisition were young age [18-24 (aRR = 4.1, 95% CI 1.6-10.8) and 25-34 (aRR = 2.7, 95% CI 1.2-5.8) years]; alcohol use (aRR = 2.6, 95% CI 1.1-6); and reported genital discharge (aRR = 3.4, 95% CI 1.6-7.2) in the past year. Condom use frequency in the year preceding enrolment was predictive of a reduced risk of HIV acquisition [sometimes (aRR = 0.4, 95% CI 0.2-0.8); always (aRR = 0.1, 95% CI 0.02-0.9)]. In the follow-up risk analysis, young age [18-24 (aRR = 6.2, 95% CI 2.2-17.3) and 25-34 (aRR = 2.3, 95% CI 1.1-5.0) years], reported genital discharge (aRR = 2.5, 95% CI 1.1-5.5), serological syphilis (aRR 3.2, 95% CI 1.3-7.7) and the partner being ART naïve (aRR = 4.8, 95% CI 1.4-16.0) were independently associated with HIV acquisition. There were no seroconversions among participants who reported consistent condom use during the study. Conclusions The study has identified important risk factors for HIV acquisition among HIV discordant couples. HIV-uninfected partners in discordant couples may be a suitable population for HIV vaccine efficacy trials. However, recent confirmation that ART reduces heterosexual HIV transmission may make it unfeasible to conduct HIV prevention trials in this population.